The impact of the COVID-19 pandemic on the national HPV immunization program in Malaysia - Rao, Sharvina Ramesh; Kampan, Nirmala; Chew, Kah Teik; Shafiee, Mohamad Nasir (Frontiers in Public Health, 2022)
In Malaysia, the HPV immunization program has been introduced since 2010 as part of the national immunization plan for female students aged 13 years old. It was a very successful immunization program with good responses from students and parents until the start of COVID-19 pandemic in 2020. The COVID-19 pandemic caused the schools to be closed and resulted about 225000 female students aged 13 years old either missed their vaccination or have incomplete doses of HPV vaccination in 2020 and 2021. This could possibly lead to an increase in cases of cervical cancer and genital warts in the upcoming years. Hence, a wellorganized catch-up HPV vaccination program is vital in ensuring the aim of achieving zero HPV-related infections in the future.